U.S. CULTURE: DIVERSITY AND INTEGRATION - Azimjon Ahmedov,; Rejapova Oydinoy, (TADQIQOTLAR, 2026)
Abstract: This article presents a scholarly analysis of the cultural landscape of the United States, focusing on the dual processes of diversity and integration that have shaped the nation since its founding. Drawing on historical sources, demographic data, and sociological theory, the study examines how successive waves of immigration, indigenous  heritage,  and  the  legacy  of  slavery  have  produced  one  of  the  most heterogeneous societies in the modern world. The research applies qualitative content analysis and comparative-historical methods to evaluate the explanatory power of three competing  models  —  the  “melting  pot,”  the  “salad  bowl,”  and  contemporary multiculturalism — in describing American cultural reality. Findings indicate that no single model fully captures the complexity of U.S. society; rather, integration occurs through  overlapping  mechanisms  including  civic  nationalism,  economic  mobility, public education, popular culture, and intermarriage, while distinct ethnic, religious, and  regional  identities  continue  to  flourish.  The  article  also  addresses  persistent challenges such as racial inequality, linguistic tensions, and political polarization. The conclusions suggest that American cultural identity is best understood as a dynamic equilibrium  between  unity  and  pluralism,  in  which  the  meaning  of  “American”  is continuously renegotiated.